The relationship between intimate partner violence and child malnutrition: a retrospective study in 29 sub-Saharan African countries - Lin, Kunhong; Zhou, Pengxiang; Liu, Mengyuan; Chen, Botian; Zhou, Zibei; Zhang, Yijia; Zhou, Ying; Jiang, Yanan; Bao, Shuyun; Chen, Dijia; Zhu, Yu; Xing, Yan (Frontiers in Public Health, 2024)
Introduction and background Intimate partner violence (IPV) and child malnutrition are global public health issues. Assessing the association between IPV and child anthropometric failures (stunting, underweight, and wasting) in 29 Sub-Saharan African (SSA) countries can provide significant global health solutions. Some studies have found an association between IPV against women and child malnutrition, but the conclusions are inconsistent. The physical and psychological conditions, living environment, and rights of the mother may be involved. Methods We collected and analyzed the Demographic and Health Surveys data (2010–2021) of 29 SSA countries. The main exposure variables were various types of IPV, classified as physical, sexual, and emotional violence. The outcome was the child’s development index, which can be roughly divided into stunting, wasting, and underweight. An adjusted binary logistic regression model was used to test the relationship between IPV and children’s nutritional status. Results A total of 186,138 children under 5 years of age were included in the analysis; 50,113 (27.1%) of the children were stunted, 11,329 (6.1%) were wasted, and 39,459 (21.3%) were underweight in all regions. The child’s gender, age, duration of breastfeeding, complementary feeding, and vitamin A supplements intake in the past 6 months were associated with their nutritional status (p < 0.001). Sexual violence was the strongest factor associated with stunting, which remained statistically significant after controlling all variables (AOR = 1.11; 95% CI: 1.02, 1.21; p = 0.012). We also found a small negative association between wasting and IPV. For underweight, there were no associations with IPV after controlling for all variables (p > 0.05). Conclusion IPV is positively associated with child stunting in SSA countries. Sexual violence showed a strong positive correlation with stunting. Wasting was unexpectedly negatively associated with IPV. There was no clear correlation between underweight and violence.